Co‐Extrusion of Multilayer Glass Fiber‐Optic Preforms: Prediction of Layer Dimensions in the Extrudate. Issue 1 (21st November 2012) - Bhowmick, Kaustav; Morvan, Herve P.; Furniss, David; Seddon, Angela B.; Benson, Trevor M.; Heo, J.
<x xml:space="preserve">Abstract</x> A three‐dimensional, incompressible and noncavitating model of a glass‐stack coextrusion process, under isothermal and non‐isothermal conditions is numerically simulated by means of computational fluid dynamics. A dynamic mesh approach is taken in a domain‐subdomain type setup to simulate the transient steps in the steady‐velocity phase of the experimental co‐extrusion. The multiphase setup consists of a glass‐stack which is composed of different glass compositions. Experimentally measured glass properties, such as the temperature coefficient of the viscosity of the supercooled glass melts are used to define the flow behavior of the glasses in the starting stack when extruded. The modeled extrudate is numerically verified for transient and spatial errors, leading to the choice of a suitable mesh. Excellent agreement is found between modeling and experiment when plotting the core/cladding dimensions of a step‐index extruded fiber‐optic preform along the length of the preform. This approach can identify the stable part of the preform, in terms of constant core/cladding layer geometry, obviating costly and time‐consuming experimental iteration. Also, the modeling allows prediction of the starting glass‐stack dimensions for a specified fiber design.